Knowledge-Based Approaches to Adaptive Agriculture: An Ethnoecological Case Study of Indigenous Communities in Climate Change Adaptation - Kamakaula, Yohanes; Fenetiruma, Obadja Andris (Agro Bali : Agricultural Journal, 2024)
The research aims to understand how the local implementation of ethnoecological knowledge is integrated with adaptive farming practices to enhance agricultural resilience and environmental sustainability amidst climate change and identify factors influencing the successful adoption of these practices and their potential for broader adoption within the context of Indigenous community agriculture in similar regions. This study employs a qualitative research approach, specifically a single holistic case study. This approach allows for an in-depth exploration of knowledge-based approaches to adaptive agriculture among vegetable farmers in Dieng, Java. Data analysis technique will follow Miles and Huberman's interactive model, which involves a systematic process of data reduction, data display, and conclusion drawing. Based on the findings in the study, it was concluded that, several key factors greatly influence the successful adoption of indigenous agricultural practices. These include the active involvement of community leaders and elders who have in-depth knowledge of effective traditional practices and government support through subsidies, loans and policies that support customary land rights and sustainable agricultural practices.